Perumusan Gaya Atraktif Bola Terapung dengan Metode Eksperimen dan Pengolahan Citra Digital - Erlina Erlina; Septian Ulan Dini; Sparisoma Viridi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Abstract. Two floating object interact each other in a certain time when the initial separation distance of them is not greather than the radius. This interaction is caused by asymmetric deformation in the liquid-air boundary plane due to contact with spherical particles. Asymmetric deformation plane of the liquid-air boundary between the two spheres and outside the sphere results an attractive force. This force is experienced by two balls that interact in a certain period of time until they come close to each other and after contact they will bond and difficult to escape. The position of each ball is observed using a video camera with 25 fps specifications and processed using Python and OpenCV and obtained data on the position of the center of mass of the system at any time until both are in contact. From the equation of position to time, the acceleration value of the ball is obtained, so that the magnitude of the attractive force can be known. The attractive force of the object is varied with the density of the object.